1999
DOI: 10.1007/bf02482779
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of performing ultrasound-guided fine-needle aspiration biopsy following mass screening for thyroid tumors to avoid unnecessary surgery

Abstract: Thyroid masses are a common clinical finding, and their management remains controversial. The purpose of this study was to evaluate the clinical effect of performing routine ultrasound (US) examinations and US-guided fine-needle aspiration biopsy (US-FNAB) in the management of diffuse or nodular goiter diagnosed by mass screening. Mass screening carried out from 1993 to 1996 revealed 444 women with goiter, 322 of whom had diffuse goiter and 122 had nodular goiter. All of these patients underwent US examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…In addition, the recent advances in high-resolution, real-time ultrasonography and the widespread use of ultrasound-guided FNAB have gradually led to changes in thinking regarding the characteristics of small carcinomas and their management. 17 Miki et al 18 reported that intraglandular metastasis and nodal spread were not related to tumor size, thus suggesting that incidental thyroid cancer should be treated in the same manner as clinical thyroid carcinoma. Numerous studies have reported on the recurrence, metastasis, and mortality associated with small thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the recent advances in high-resolution, real-time ultrasonography and the widespread use of ultrasound-guided FNAB have gradually led to changes in thinking regarding the characteristics of small carcinomas and their management. 17 Miki et al 18 reported that intraglandular metastasis and nodal spread were not related to tumor size, thus suggesting that incidental thyroid cancer should be treated in the same manner as clinical thyroid carcinoma. Numerous studies have reported on the recurrence, metastasis, and mortality associated with small thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the pathologic interpretation of the lesion, a ''conclusive'' biopsy would lead to either surgery or observation, whereas an ''inconclusive'' biopsy would be followed up with another ultrasound-guided FNAB. [15][16][17][18] Repeat biopsy samples deemed ''conclusive'' would lead to the appropriate intervention of either surgery or observation, and all ''inconclusive'' samples would, again, lead to diagnostic hemithyroidectomy.…”
Section: Methodsmentioning
confidence: 99%
“…However, the beneficial effect of US on the positive predictive value of FNAC is not considered by most of these investigators. 22 …”
mentioning
confidence: 99%